A robust adaptive neural controller to drive a knee joint actuated orthosis - Mefoued, S.; Daachi, M. E.; Daachi, B.; Mohammed, S.; Amirat, Y. (2012 IEEE International Conference on Robotics and Biomimetics, 2012)
This paper presents a robust adaptive control of an actuated orthosis intended to assist the lower limb movements of dependent persons. The proposed controller, based on a MultiLayer Perception Neural Network (MLPNN) and considered as a black-box, does not require the dynamic model of lower limbs/orthosis. A neural identification is used to extract the principal components of the MLPNN input vector. The MLPNN is used to compensate the dynamic effects arising from the interaction between the human lower limb and the orthosis. MLPNN weights are adjusted online according to an adaption algorithm based on the Lyapunov analysis. Experiments, carried out on a healthy subject, show the good performance of the proposed controller in terms of trajectory tracking and robustness against external disturbances.